Effects of stopped and reduced training on irisin and metabolic parameters in professional female basketball players - Heidari, A.; Jafari, A. (German Journal of Exercise and Sport Research, 2025)
Abstract Purpose: Irisin, a significant myokine released during physical exercise, plays a crucial role in promoting glucose metabolism. This study aimed to compare the effects of a 4-week exercise cessation and reduction phase conducted during the off-season (OS) on serum irisin and metabolic parameters in professional female basketball players. Methods: Thirty-four professional female basketball players from the division I level league (age: 22.4 ± 1.73 years, body mass index [BMI]: 22.93 ± 0.91 kg/m2), who completed a 12-week competitive season (CS) complex training program, were randomly assigned to two groups: the exercise cessation group (EC; n = 16) and the exercise reduction group (ER; n = 16). Irisin, insulin, glucose, homeostasis model assessment-estimated insulin resistance (HOMA-IR), triglycerides (TG), high-density lipoprotein (HDL), and total cholesterol (TC) were measured at three time points: after the CS (T0), 2 weeks later (T2), and 4 weeks later (T4) in the OS, all while in a fasting state. Results: After 4 weeks, both groups showed a reduction in irisin levels (p < 0.05), but the reduction in the EC group was greater (EC group 19.66% vs. ER group 12.23%). However, a significant decrease was observed in insulin and irisin/HOMA-IR (p < 0.01), glucose, and HOMA-IR (p < 0.05) in the EC group. Conclusion: Irisin appears to be affected by changes in physical activity levels. Incorporating light exercise during the OS phase may help reduce the decline in irisin levels and maintain metabolic health by preserve glucose levels and insulin resistance in professional female basketball players. These findings emphasize the importance of tailored off-season training strategies for athletes and provide insights for optimizing performance and well-being during the transition from the competitive season to the off-season.